2015
DOI: 10.1089/jmf.2014.3222
|View full text |Cite
|
Sign up to set email alerts
|

Angelica keiskeiKoidzumi Extracts Improve Some Markers of Liver Function in Habitual Alcohol Drinkers: A Randomized Double-Blind Clinical Trial

Abstract: Alcohol induces oxidative stress and inflammatory response, which can lead to hepatitis and cirrhosis. Previous studies reported that the extracts of Angelica keiskei Koidzumi (AKE) have antioxidant and anti-inflammatory properties, suggesting that AKE could improve abnormalities associated with alcoholic liver disease. In this study, the effectiveness of AKE supplementation was assessed in 82 habitual alcohol drinkers (male: more than 14 units per week, female: more than 7 units per week) with abnormal liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A. keiskei has long been used as a herbal medicine due to its antioxidant effects ( 33 ). A. keiskei contains bioactive substances, such as chalcone, coumarin, saponin, and flavonoids ( 34 , 35 ). Several studies have demonstrated that A. keiskei extract has beneficial effects on alcoholic liver diseases ( 34 ), antioxidant ( 33 ), anti-cancer ( 35 ), and anti-inflammatory effects ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A. keiskei has long been used as a herbal medicine due to its antioxidant effects ( 33 ). A. keiskei contains bioactive substances, such as chalcone, coumarin, saponin, and flavonoids ( 34 , 35 ). Several studies have demonstrated that A. keiskei extract has beneficial effects on alcoholic liver diseases ( 34 ), antioxidant ( 33 ), anti-cancer ( 35 ), and anti-inflammatory effects ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…A. keiskei contains bioactive substances, such as chalcone, coumarin, saponin, and flavonoids ( 34 , 35 ). Several studies have demonstrated that A. keiskei extract has beneficial effects on alcoholic liver diseases ( 34 ), antioxidant ( 33 ), anti-cancer ( 35 ), and anti-inflammatory effects ( 36 ). A. keiskei extract was reported to prevent D-galactosamine-induced hepatic failure in rats ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical trial for habitual alcohol drinkers with abnormal liver function tests also showed that intake of the extracts significantly reduced c-glutamyl transferase (GGT) levels (Noh et al 2015). A patent is filed on the beneficial activity of an ethanol extract of the roots to improve liver functions and relieve fatigue (Kim et al 2006).…”
Section: Hepato-protective Activitymentioning
confidence: 99%
“…In addition, AK has widely been utilized among Koreans that believe it can protect against hepatotoxicity. Noh et al [8] recently reported that an AK extract supplement can improve liver function in heavy drinkers. However, the effects of AK on hepatotoxicity and its mechanisms of action have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%